Neuropathic Pain In Leprosy: Prevalence, Patterns, And Impact In The World’s Three Most Affected Countries - Isna Zalwa Noor Fajri; Retno Indrastiti Retmono; Galih Sari Damayanti (Universitas Pahlawan Tuanku Tambusai, 2026)
Leprosy remains highly endemic in India, Brazil, and Indonesia, where neurological complications continue to drive long-term disability despite the availability of effective multidrug therapy. Neuropathic pain has increasingly been recognized as a major contributor to morbidity among individuals affected by leprosy; however, evidence from the highest-burden regions remains fragmented. This study aims to systematically synthesize current evidence on the burden, characteristics, and impact of neuropathic pain in people with leprosy in India, Brazil, and Indonesia. A systematic search was conducted in PubMed, Cochrane Library, and ScienceDirect using predefined terms related to leprosy and neuropathic pain. Eligible studies assessed neuropathic pain using validated diagnostic tools or structured clinical evaluation, with data extracted using a standardized template and risk of bias assessed based on observational study criteria. Thirteen studies met the inclusion criteria, reporting neuropathic pain prevalence ranging from 21.8% to 75%, depending on diagnostic methods. Common symptoms included burning pain, tingling, electric-shock sensations, and dysesthesia, frequently accompanied by sensory loss and nerve thickening. Notably, neuropathic pain often persisted after completion of multidrug therapy, indicating ongoing neural dysfunction beyond bacteriological cure. Overall, neuropathic pain represents a prevalent, disabling, and under-addressed complication of leprosy, highlighting the urgent need for routine screening, long-term follow-up, and integrated multidisciplinary care in high-burden countries.